Ambient Intelligence - Software and Applications: 6th International Symposium on Ambient Intelligence (ISAmI 2015) - Mohamed, A (Springer, 2015)
This volume contains the proceedings of the 6th International Symposium on Ambient Intelligence (ISAmI 2015), held in Salamanca, Spain on June 3th-5th at the University of Salamanca. After a careful review, 27 papers from 10 different countries were selected to be presented in ISAmI 2015 at the conference and published in the proceedings.